Instilling Moral and Religious Values in Early Childhood in Aster Gorontalo Kindergarten - M. Husain, Rizky; Syarifah, Syarifah; A. Humalidi, Cindy; R. Cahyani, Putry (PT Literasi Nusantara Publisher, 2022)
Problems regarding the inculcation of moral and religious values in early childhood often occur from a poor environment, limited time for parents to meet their children, grandmothers who spoil their grandchildren too much, the absence of examples of good behavior from parents, and the absence of social restrictions. Early childhood needs to be taught and instilled with moral and religious values in their daily lives. Instilling moral and religious values plays an important role in the form of children's behavior so that children are able to interact and behave according to their growth and development. Moral education is very important to be taught to children from an early age. Especially nowadays where the influence of friends or social media is very large. This is also related to affective education in early childhood where these are interrelated, namely affective education means education for social-individual development, feelings, emotions, morals, and ethics. With the inculcation of moral and religious values along with effective education in schools, teachers are expected to be able to guide students so that the ethics and behavior of children are polite and have noble character.